2019
DOI: 10.1002/jum.15012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound Parameters in Carpal Tunnel Syndrome: Additional Criteria for Diagnosis

Abstract: Objectives To determine the diagnostic capacity of ultrasound (US) in detecting carpal tunnel syndrome (CTS). Methods Volunteer adults with and without CTS symptoms were recruited from offices in metropolitan Manila, where employees’ work was hand/wrist intensive. Carpal tunnel syndrome was independently diagnosed by a reference standard (positive findings on a physical examination and nerve conduction studies). Blinded US measurements were taken of the median nerve (cross‐sectional area, hypervascularity, wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies presented mixed results with one study showing 2 mm of palmar bowing to have a 44% sensitivity and 85% specificity in identifying patients with CTS. 31,32 Other studies showed palmar bowing at the carpal tunnel inlet (between the scaphoid and pisiform) to be a specific sign of CTS with a threshold of 1 mm demonstrating a specificity of 97%. 28 Median nerve hypervascularity on Doppler US is a specific although insensitive sign of CTS, with one study demonstrating a sensitivity of 69% and specificity of 95%.…”
Section: Normal Imaging Appearancementioning
confidence: 99%
See 1 more Smart Citation
“…Studies presented mixed results with one study showing 2 mm of palmar bowing to have a 44% sensitivity and 85% specificity in identifying patients with CTS. 31,32 Other studies showed palmar bowing at the carpal tunnel inlet (between the scaphoid and pisiform) to be a specific sign of CTS with a threshold of 1 mm demonstrating a specificity of 97%. 28 Median nerve hypervascularity on Doppler US is a specific although insensitive sign of CTS, with one study demonstrating a sensitivity of 69% and specificity of 95%.…”
Section: Normal Imaging Appearancementioning
confidence: 99%
“…Cutoffs of 2.5 and 3 have been used, and in general, flattening ratio is not a sensitive or specific sign for identifying cases of CTS. 28,31,32 Median nerve CSA can also be measured just distal to the carpal tunnel outlet with one study showing a CSA > 14 mm 2 to have a sensitivity of 64% and specificity of 100% in identifying cases of CTS. 28 MRI is less commonly performed for suspected CTS and has been less extensively studied than US.…”
Section: Normal Imaging Appearancementioning
confidence: 99%
“…5,6 US-based morphological parameters for detecting CTS are an increased cross-section area (CSA) of the MN at the carpal tunnel inlet or outlet, flattening of the MN, and bowing of the transverse carpal ligament (TCL) at the level of the carpal tunnel outlet. [7][8][9] Elastography has been proven as a useful adjunct US method in CTS evaluation. 10 Therapeutic recommendations for CTS depend on disease severity and may include anything from a conservative approach to surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Elsaman, et al [ 10 ] introduced a diagnostic criterion for CTS—the depth of the carpal tunnel (DCT), which is defined by the distance from the surface of the flexor retinaculum to the highest point of the capitate bone. To accommodate individual anthropometric variability, the wrist:forearm ratio (WFR), wrist–forearm difference (WFD), median-to-ulnar nerve ratio (MUR) and median-to-ulnar nerve difference (MUD) were also suggested as diagnostic criteria for CTS [ 11 , 12 , 13 , 14 , 15 ]. In addition, increased intraneural vascularity of the MN was also reported in patients with CTS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased intraneural vascularity of the MN was also reported in patients with CTS [ 16 , 17 ]. Gonzalez-Suarez et al [ 11 ] revealed that combining the WFD obtained by grayscale sonography and intraneural hypervascularity obtained by color Doppler could provide better sensitivity of up to 98.1%. Some researchers [ 18 , 19 ] further utilized elastography to observe the changes in the nerve environment and tissue elasticity.…”
Section: Introductionmentioning
confidence: 99%